Evaluation of an Initial Specimen Diversion Device (ISDD) on Rates of Blood Culture Contamination in the Emergency Department - Buzard, Blake A. (Kans J Med, 2021)
INTRODUCTION: Blood cultures are the gold standard for identifying bloodstream infections. The Clinical and Laboratory Standards Institute recommends a blood culture contamination rate of less than 3%. Contamination can lead to misdiagnosis, increased length of stay and hospital costs, unnecessary testing, and antibiotic use. These reasons led to the development of initial specimen diversion devices (ISDD). The purpose of this study was to evaluate the impact of an initial specimen diversion device on rates of blood culture contamination in the emergency department. METHODS: This was a retrospective, multi-site study including patients who had blood cultures drawn in an emergency department. February 2018 to April 2018, when an ISDD was not utilized, was compared with June 2019 to August 2019, when an ISDD was being used. The primary outcome was total blood culture contamination. Secondary outcomes were total hospital cost, hospital and intensive care unit length of stay, vancomycin duration of use, vancomycin serum concentrations obtained, and repeat blood cultures obtained. RESULTS: A statistically significant difference was found in blood culture contamination rates in the pre-ISDD group vs. the ISDD group (7.47% vs. 2.59%, p < 0.001). None of the secondary endpoints showed a statistically significant difference. CONCLUSIONS: Implementation of an ISDD reduced blood culture contamination. When implementing the ISDD to a healthcare system, compliance is important and will affect contamination rates dramatically.